Continuous measurements of the ozone concentration in the Arctic Airborne Measurement Program 1998 (AAMP98) - Shinji Morimoto (National Institute of Polar Research, 2002)
Continuous measurement of the ozone concentration was carried out on board a jet airplane as a part of the ‘Arctic Airborne Measurement Program 1998 (AAMP 98)' from March 6 to 14, 1998. A newly developed ozone measurement system used in AAMP 98 was capable of precise determination of the ozone concentration from ground level to about 13 km height every 12 s. The ozone data obtained by our system over Svalbard, Norway, agreed well with those by routine ozone sondes. The ozone and CO2 concentration data clearly showed negative correlations at a constant pressure level of 195 hPa between Barrow, U.S A. and Longyearbyen, Norway. These results suggest that the 'in situ' ozone data obtained on board an airplane provides useful information for exchange processes between the troposphere and stratosphere as a tracer of stratospheric air.